Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Rhamnogalacturonan I in commercial samples of polygalacturonic acid is a functional driver: A study of isolation, structural elucidation, role in immunostimulation and hydrogel mechanics - Xueting Zhang; Chuying Huo; Pengfei Shan; Niping Chen; Quanwei Zhang; Hauyee Fung; Wenting Zhao; Jing Li; Peili Zhu; Shanlong Tang; Ye Yuan; Lin Sun; et al. (Food Hydrocolloids, 2026)

Defect-engineered Cu-TCPP/ZIF-L nanosheet-modified PVDF membrane with enhanced water purification and dye removal performance - Yiming Zhao; Jingyuan Zhang; Junmei Liu; Jiatong Han; Dan Xu; Jing Wang; Fengzhi Lyu; Lin Qin; Donghui Xu; Ge Chen; Guangyang Liu (Chemical Engineering Journal, 2026)

Temporal sulfur redox reprogramming enables control-oriented intensification of sulfur-based autotrophic denitrification - Kun Zheng; Han-Bing Xiao; Yi-Lu Sun; Zhou-Yang Li; Jing-Zhe Zhang; Han-Lin Wang; Ai-Jie Wang; Xue-Ning Zhang (Water Research, 2026)

Preparation of plant-based meat analogues by soft matter method: Effects of NaCl concentrations and addition order - Jing-Wen Zhang; Qin Yang; Hui-Lin Li; Qing-Xuan Liu; Han-Qing Chen (Food Hydrocolloids, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Mechanisms of Dissolved Organic Matter Migration in Coal Mining Subsidence Areas - Jing Xu; Liangmin Gao; Jinxiang Yang; Jieyu Xia; Han Song; Yanjun Liu; Kai Zhang; Lin Wu; Xin Shu (Mine Water and the Environment, 2026)

LC-MS-based metabolomics reveals the In Vivo effects of cognitive formula 1 in rats with Aβ-induced Alzheimer’s disease - Di Wu; Yanling Lin; Wenjun Guo; Zengling Wang; Yan Chang; Jing Yan; Daqing Han; Ke Xiang; Zhen Yang (Experimental Brain Research, 2026)

Species Diversity, Parasitism Rates, Longevity, and Population Dynamics of the Parasitoid Complex Attacking Ophelimus bipolaris in China - Jin Hu; Yuan-Hao Li; Jing-Hui Su; Jin-Bo Sun; Guo-Bao Qin; Yan Qin; Lai-Feng Luo; Lin-Xia Feng; Kai-Jian Han; Zoya Yefremova; Jun Li; Xia-Lin Zheng (Neotropical Entomology, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

ROMO1 loss in cholinergic neurons induces mitochondrial ultrastructural damage and ALS-like neuromuscular degeneration - Wei Nie; Zhiwen Jing; Linling Cheng; Lin-Lin Li; Yuxiao Bai; Fengli Xu; Sihan Li; Limei Lin; Xiaohui Dong; Liping Yu; Lei Cai; Bingxing Pan; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Numerical investigation with viscosity of nonlinear wave forces on a dual-tube submerged floating tunnel - Hong-fei Mao; Kai-lin Chen; Long Han; Zhong-bing Zhou; Yan-li He; Li-min Wang; Jing Xie (Ocean Engineering, 2026)

MRI-guided nano-prodrug with self-detoxifying bioclearance for precision detection and therapy of cancer metastases - Wenyi Zhang; Dengyi Duan; Jing Peng; Lin Chen; Kangkang Liu; Yiming Li; Jianmin Li; Gang Han; Yang Zhao (Chemical Engineering Journal, 2026)

Impacts of carbonaceous aerosols from summer crop residue burning on air quality, radiation and meteorology over east China - Yuanyuan Zheng; Jian Wu; Zhiwei Han; Jiawei Li; Jie Li; Yunfei Wu; Jing Wang; Lin Liang (Theoretical and Applied Climatology, 2026)

Correction: Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Drying-wetting cycles alter the balance between physical fragmentation and leaching during leaf litter decomposition: a laboratory incubation experiment - Le-Lin Yu; Rui-Jing Chai; Qi-Han Tu; An He; Le-Cheng Ai; Rong Mao (Plant and Soil, 2026)

Stand age drives divergent microbial metabolic limitations and ecosystem multifunctionality between rhizosphere and bulk soils in subtropical Cryptomeria japonica plantations - Shanshan Huang; Yi Jian; Jing Li; Dengjie Zhou; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Lixia Wang; et al. (Soil Ecology Letters, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Detrital zircon UPb and fission track double dating constraints on the exhumation history of Longmen Mountains: New insights into proto-Tibetan Plateau evolution - Xu Lin; Siyu Han; Lin Wu; Marc Jolivet; Dongliang Liu; Zhonghai Wu; Weiming Liu; Jing Liu-Zeng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Co-occurrence and regulation of nanoplastics and typical flame retardant in anammox process: Potential risk and molecular mechanism - Jing-Ao Jin; Na-Na Han; Wei-Lin Guo; Qiu-You Xu; Jiao-Jiao Wang; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Ultrasound-assisted dry-heating glycosylation with xylooligosaccharides: Enhancing the structural and functional properties of pig skin collagen - Shengqi Jiang; Lin Li; Hongqing Nie; Jincheng Han; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Huiyu Han; Jing Xi; Wu Ding (Food Hydrocolloids, 2026)

Molecular engineering for bitterness masking of natural products: from decoding structure-taste relationships to structure-driven bitterness suppression - Linjie Tian; Jiao Song; Jiaxin Li; Jing Wu; Haozhou Huang; Junzhi Lin; Li Han; Hongyan Ma; Dingkun Zhang (Critical Reviews in Food Science and Nutrition, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Mechanism study on ultrasonication combined with soybean 11S globulin to improve the quality and flavor compounds of low-salt lamb meat gel - Rong Bai; Hongqing Nie; Jing Xi; Aitmagambetova Madina; Lin Li; Huiyu Han; Shengqi Jiang; Gege Wang; Wu Ding (Meat Science, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Irradiation co-succinylation modification of caprine casein: Impact on physicochemical properties, molecular structure, and functional properties - Jing Xi; Huiyu Han; Rong Bai; Madina Aitmagambetova; Siying Wang; Shengqi Jiang; Hongqing Nie; Lin Li; Xiang Ye; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

An oriented freezing strategy for fabricating fibrous structures of plant-based chicken analog - Yao Lin; Yu Peng; Li Shen; Qiuyu Han; Quanhong Li; Xiaojun Liao; Jing Zhao (Food Hydrocolloids, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

A novel multimodal combining radiomics and tumor–stroma ratio (TSR) improves diagnosis of gastric cancer peritoneal metastasis - Lin Zhong; Ting Lin; Dong Hou; Hongyun Huang; Shihai Zhou; Yu Lin; Yue Yu; Liangquan Liu; Jing Luo; Fanghai Han; Lang Xie (Clinical & Experimental Metastasis, 2026)

Effects of A-site cations (Sm, Y, Gd) on methanol oxidation over AMn2O5 mullite catalysts - Liangzheng Lin; Zhitao Han; Junhao Jing; Shoujun Zhang; Shaoqin Sheng; Sihan Yin; Tingjun Liu; Chuanqiu Gao (Fuel, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Characteristics of benthic microeukaryotic communities in different ecosystems of the Yellow River Estuary salt marshes - Jing Han; Lin Sun; Junrong Liang; Yahui Gao; Changping Chen (Estuarine, Coastal and Shelf Science, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Interfacial charge modulation in CuFe2O4/MXene composites: Enhancing persulfate activation and efficient degradation of chloroquine phosphate - Yeqiong Huang; Zhi Song; Boxia Liu; Lin Wang; Xiayan Zhang; Jialu Liu; Dongxu Han; Chuhan Xing; Jing Zhang (Journal of Environmental Chemical Engineering, 2025)

Hydrocarbon generation and pore evolution in marine organic-rich shales across maturation stages - Xueying Wang; Kun Zhang; Zhenxue Jiang; Yanhua Lin; Yan Song; Chengzao Jia; Shu Jiang; Lin Jiang; Hulin Niu; Jing Li; Yunbo Zhang; Xingmeng Wang; et al. (Fuel, 2025)

Dendrobium officinale polysaccharide inhibits M1 macrophage polarization via activating SENP1-SIRT3 signaling and alleviates ulcerative colitis - Jing Zhang; Xiaohe Lin; Huaying Song; Yumin Xie; Shaozhen Hou; Song Huang; Xianhua Du; Hailun Li; Yun Han; Jian Liang; Xiaoyan Jiang (Food Research International, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

The mechanism of p38 MAPK, NF-κB, and IL-6 in T-2 toxin and/or selenium deficiency induced spleen injury - Xiang Xiao; Rongqi Xiang; Jiaxin Liu; Ziwei Guo; Haobiao Liu; Xue lin; Miaoye Bao; Viscardi Angelo; Jing Han (Immunologic Research, 2025)

Research on the Characteristics of Deep and Medium-Level Geothermal Energy for Highway Ice Melting and Snow Removal - Taking the Jinan-Ningjin Expressway as an Example - Chuang-shan Wu; Zhao-di Han; Wen-xiang Yang; Jing-kai Qu; Zhao-feng Zheng; Fan-meng Kong; Kun Liang; Lin-zhi Lang (Applied Geophysics, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

An activatable aptamer probe Q2c for detection of grouper iridovirus - Mingzhu Liu; Jing Huang; Lin Huang; Qiwei Qin; Yanlei Chang; Lei Shi; Yun Sun; Yongcan Zhou; Shaowen Wang; Shuyu Han; Qing Yu; Pengfei Li (Aquaculture, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Chemical constituents isolated from leaves of seashore plant Aglaia rimosa - Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung; Wei-Yu Lin; Zhen-Hong Han; You-Ying Chen; Chun-Lin Chen (Phytochemistry Letters, 2025)

Single-electrode multiplex sensing via metal ion displacement method - Yiming Zhang; Zhi Chen; Songrui Wei; Huiling Lin; Yujun Zhang; Yingxia Liu; Jing Wang; Qi Gao; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Interinterface electron-proton co-engineering: The dual regulation of surface charge and hydroxylation promotes the efficient activation and degradation of chloroquine phosphate by monopersulfate - Zhi Song; Yeqiong Huang; Boxia Liu; Hongqiao Jiao; Yulong Ma; Lin Wang; Xiayan Zhang; Jialu Liu; Dongxu Han; Chuhan Xing; Jing Zhang (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Application of spectral induced polarization technique in monitoring zinc removal by activated carbon as a permeable reactive barrier material - Sheng Zhou; Yi-Xin Yang; Jing-Jing Cao; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Contaminant Hydrology, 2025)

Novel nanoceria in situ-derived porphyrin heterostructure enhanced electrochemiluminescent and colorimetric dual-mode detection of tetracycline residue in foods - Xueran Shi; Yingbo Cao; Lin Cong; Tiance Gu; Jing Wang; Qian Han (Food Chemistry, 2025)

Alleviating moxifloxacin-induced biological inhibition in ethanol and Cl− coexisted wastewater: Why UV/H2O2 is better than Fenton - Yingying Zhang; Min Yang; Wenbo Cui; Lin-Ji Xu; Depeng Zhang; Yu Tao; Jing-Long Han; Aijie Wang (Chemical Engineering Journal, 2025)

An efficient network with state space model under evidential training for fetal echocardiography standard view recognition - Changzhao Chen; Yiman Liu; Tongtong Liang; Shibin Lin; Xiaoxiang Han; Xiaohong Liu; Jing Yang; Yuqi Zhang; Xueping Yan (Medical & Biological Engineering & Computing, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Heavy metal pollution enhances herbivore resistance of male poplars over females through modifying volatile-mediated tritrophic interactions - Tiantian Lin; Xiaotao Han; Guoqing Zhu; Wanci He; Lianghua Chen; Jing Li; Yan Wang; Tao Li (Journal of Hazardous Materials, 2025)

Galnt3, an enzyme engaged in protein glycosylation modification, is essential for the maintaining of intestinal health in zebrafish - Jing Gao; Wenjin Li; Jingyuan Lin; Yilin Han; Guangdong Ji; Zhenhui Liu (Fish & Shellfish Immunology, 2025)

Exploring the role of the rhizosphere in soil carbon cycling: impacts on pools and components of SOC along a chronosequence of Cryptomeria japonica plantations in subtropical China - Dengjie Zhou; Yaling Yuan; Jing Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Li Zhang; Hongwei Xu; Lixia Wang; Sining Liu; et al. (Plant and Soil, 2025)

Efficient antibiotic tetracycline degradation and toxicity abatement via the perovskite-type CaFexNi1-xO3 assisted heterogeneous electro-Fenton system - Yuling Liang; Aochen Feng; Naif Abdullah Al-Dhabi; Jing Zhang; Wenle Xing; Tao Chen; Yuxuan Han; Guangming Zeng; Lin Tang; Wangwang Tang (Water Research, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

Ecological impacts of treated effluent on multitrophic biodiversity and their interactions - Wei Xiong; Ting Chen; Xun Du; Lin Hou; Yiyong Chen; Jing-Long Han; Aibin Zhan (Environmental Research, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Soil nutrients determine multidimensional absorptive root traits of Cryptomeria japonica var. sinensis plantations along a chronosequence in subtropical forest - Chunran Liu; Lihua Wang; Jing Li; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Hongwei Xu; Li Zhang; Lixia Wang; et al. (Journal of Environmental Management, 2025)

CRISPR CLAMP: Attomolar level of multiple miRNAs - Yiming Zhang; Zhi Chen; Songrui Wei; Jing Wang; Yujun Zhang; Huiling Lin; Hai Fu; Yingxia Liu; Qi Gao; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Solar evaporator coupled with strong/weak convection and its cascade utilization - Zhengtong Li; Jia-Han Zhang; Jing Zhang; Peng Yan; Tao Yang; Chao Yang; Peng Lin; Taotao Meng; Meng An; Yingtang Zhou; Xingtao Xu (Science Bulletin, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

T-2 toxin induces cardiac fibrosis by causing metabolic disorders and up-regulating Sirt3/FoxO3α/MnSOD signaling pathway-mediated oxidative stress - Lichun Qiao; Xue Lin; Haobiao Liu; Rongqi Xiang; Jingming Zhan; Feidan Deng; Miaoye Bao; Huifang He; Xinyue Wen; Huan Deng; Xining Wang; Yujie He; et al. (Journal of Environmental Sciences, 2025)

Hysteresis elongation behavior of RC beams failing in different modes: Experimental investigation and numerical modelling using smeared crack approach - Zi-Nan Wu; You Dong; Xiao-Lei Han; Jing Ji; Jing-Cong Lin (Engineering Structures, 2025)

Mechanical properties and microstructure of fly ash and slag-based geopolymer prepared by silica fume-based activator - Minguo Lin; Geng Chen; Yonghui Chen; Dandan Han; Ruobin Su; Jing Wu (Journal of Cleaner Production, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

American ginseng fruit: Antioxidant capacity, bioactive components, and biosynthesis mechanism during development - Yujuan Zhang; Lijuan Hou; Jing Hu; Xianchang Wang; Shujing Guo; Hongqing Xie; Yun Zhou; Wen Ai; Lin Li; Xin Wang; Li Ren; Fangzhou Zhao; et al. (Food Research International, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Metabolomics Revealed Cadmium Exposure Associated with Alterations in Serum Metabolism in Children - Miaoqian Li; Ping Wan; Lichun Qiao; Xinyue Wen; Huan Deng; Xue Lin; Jingke Lei; Jing Han (Biological Trace Element Research, 2025)

Geotrichum candidum AGRC-GC1 prevented the decay of pulp from Citri Reticulatae Pericarpium production by inhibiting the growth of spoilage microorganisms - Xue-Ying Han; Jing-Yi Hu; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li; Shuang Li; Jun-Jin Deng (Food Bioscience, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

A high selective separation method for high-purity polysaccharides from dandelions by density-oriented deep eutectic solvent ultrasonic-assisted system - Han Zhang; Yu Lin; Yanan Bao; Wen-Jing Li; Bo Hong; Min Zhao (Sustainable Chemistry and Pharmacy, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Unraveling the effects of prenatal anesthesia on neurodevelopment: A review of current evidence and future directions - Qiu-Xia Xiao; Min-Jian Geng; Qiu-Lin Wang; Chang-Le Fang; Jing-Han Zhang; Qi Liu; Liu-Lin Xiong (NeuroToxicology, 2024)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

Impacts of distinct residual aluminum on gypsum scaling in nanofiltration: Identification of key species - Jinjin Jia; Jinlong Wang; Dachao Lin; Jing Zhao; Hesong Wang; Longfeng Hu; Jiaxuan Yang; Han Zhang; Guibai Li; Heng Liang (Desalination, 2024)

Improving global weather and ocean wave forecast with large artificial intelligence models - Fenghua Ling; Lin Ouyang; Boufeniza Redouane Larbi; Jing-Jia Luo; Tao Han; Xiaohui Zhong; Lei Bai (Science China Earth Sciences, 2024)

Vulnerability of Global Pine Forestry's Carbon Sink to an Invasive Pathogen–Vector System - Jiao Zhou; Jingjing Du; Luís Bonifácio; Wandong Yin; Lin Huang; Jing Ning; Dongbo Han; Jiafu Hu; Wei Song; Lilin Zhao (Global Change Biology, 2024)
The substantial contribution of northern forest growth to the global increase of biomass carbon stock is well documented. However, the ecological consequences of pest‐ and disease‐related losses in these forests have not received comparable attention. This study highlights that pine species are major contributors to carbon stocks in Northern Hemisphere. The total carbon storage of Pinus in the Northern Hemisphere was estimated at 70,726 teragrams of carbon (TgC; 17.7% of the total forest carbon 478,012 TgC), accounting for 4.9%, 28.4%, and 12.5% of the total carbon storage in the forests of Asia, Europe, and North America, respectively. However, pine trees were under threat from an invasive complex involving the pine wood nematode ( Bursaphelenchus xylophilus ) and Japanese pine sawyer beetle ( Monochamus spp.). Since 1977, this complex resulted in a carbon sink deficit of 1857 TgC (18% of the carbon currently stored in Europe's live tree biomass) in northern pine ecosystems. The carbon losses attributed to B. xylophilus exceeded those caused by wildfires, which are typically regarded as the primary factor of forest disturbances. Furthermore, the contributions of environmental variables indicate that the expected northward shift in precipitation patterns will exacerbate B. xylophilus threats, endangering 78% of the boreal forests across Eurasia by 2100. Among these high‐risk areas, 62% contributed significantly to global carbon sink, and 42% was protected forests. Following the present trend, carbon losses caused by the B. xylophilus complex could exceed 39% of the total carbon storage in terrestrial ecosystems. This study provides comprehensive datasets that detail the global distribution and high‐risk habitats of pine species and B. xylophilus vector beetles in affected countries. Our findings underscore the substantial risk of carbon losses posed by B. xylophilus to northern pine forests, with potential implications for global carbon dynamics and the achievement of international goals related to “carbon peak” and “carbon neutrality.”

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Lipid fingerprinting and geographical origin identification of large yellow croaker (Larimichthys crocea) using UHPLC-QTOF-MS - Haolei Han; Xiangxin Lin; Yuxuan Wu; Houru Li; Qi Jia; Changmin Hu; Yixuan Lin; Guangqin Liao; Yongzhong Qian; Jing Qiu (Food Research International, 2024)

Mathematical modeling and comparative metabolomics analyses of interactions between Lactiplantibacillus plantarum and Morganella morganii - Jing Han; Binkun Liu; Xinping Lin; Sufang Zhang; Liang Dong; Chaofan Ji (Food Research International, 2024)

Mineralogy and geochemistry of the Cambrain Shuijingtuo Formation black shales from Western Hubei, China: implications on enrichment of critical metals and paleoenvironment - Yuan Wang; Jing Li; Yang Lin; Xinguo Zhuang; Vanlong Hoang; Peng Wu; Xin Luo; Han Zhang; Xiaoyang Zhang (Frontiers in Marine Science, 2024)
Black shales have attracted the attention of numerous researchers not only due to their high potential as hydrocarbon source rocks and shale gas reservoirs, but also to the enrichment of critical metal elements in black shale series. Black shale of the Cambrian Shuijingtuo Formation is one of the most important black shales in the Yangtze platform. This paper conducts integrated research on the mineralogical and geochemical characteristics of this black shale from the Luojiacun section in Western Hubei Region, aiming at elaborating the enrichment mechanism of elevated critical metal elements in the Shuijingtuo black shale. Minerals in the Shuijingtuo black shale are predominantly composed of quartz (avg. 43.0%) and clay minerals (avg. 32.5%), with small proportions of calcite, albite, clinochlore, and pyrite. The Shuijingtuo black shale is characterized by high total organic carbon (TOC, avg. 3.9%) content and enriched in V-Ni-Cr-U and Sr-Ba critical metal assemblages. The elevated V, Cr, Ni, and U present dominant organic affinities, while Sr and Ba are closely correlated to calcite and pyrite, respectively. The enrichment of V-Cr-Ni-U critical element assemblages in Shuijingtuo black shale are ascribed to the high primary productivity, anoxic depositional conditions, marine biologic production, and low-temperature hydrothermal activities. The enrichment of Sr and Ba is related to the high primary productivity and anoxic depositional conditions, respectively.

Developing fine-tuned MOF membranes for highly efficient separation and adsorption of chemical pollutant in water - Jiatong Han; Donghui Xu; Yanyan Huang; Yuwei Hua; Xin Ding; Zhihao Lin; Jie Zhou; Huan Lin; Ge Chen; Jing Wang; Xiaomin Xu; Jia Liu; et al. (Chemical Engineering Journal, 2024)

Corrigendum to “An efficient approach for identifying important biomarkers for biomedical diagnosis” [Biosystems 237 (2024) 105163] - Jing-Wen Huang; Yan-Hong Chen; Frederick Kin Hing Phoa; Yan-Han Lin; Shau-Ping Lin (BioSystems, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

Xanthohumol combined with chitosan-oxidized starch film as a potential new strategy for food packaging: Characterization, physicochemical and biological properties - Fan Yang; Siyuan Chang; Lin Zhao; Jing Han; Hao Li; Sen Zhang; Sheng Guo; Jinao Duan (Food Packaging and Shelf Life, 2024)

Targeting IGF2BP1 alleviated benzene hematotoxicity by reprogramming BCAA metabolism and fatty acid oxidation - Jingyu Wang; Lin Han; Ziyan Liu; Wei Zhang; Lei Zhang; Jiaru Jing; Ai Gao (Chemico-Biological Interactions, 2024)

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

An untargeted metabolomics study of cardiac pathology damage in rats caused by low selenium diet alone or in combination with T-2 toxin - Xue Lin; Lichun Qiao; Haobiao Liu; Miaoye Bao; Huan Deng; Lianxu Jia; Xinyue Wen; Feidan Deng; Ping Wan; Yizhen Lyu; Jing Han (Food and Chemical Toxicology, 2024)

Detecting viscosity changes in the limb ischemia-reperfusion in mice with a near-infrared fluorescence probe - Hui Peng; Xinying Jing; Song Han; Weiying Lin (Analytica Chimica Acta, 2024)

Phosphine oxide balanced charge transfer hybridization in multi-resonance emitters: towards ∼40% external quantum efficiency and preserved color purity - Su Chen; Yidan Wang; Jincheng Lin; Rundong Tian; Shuang Li; Yi Man; Shuo Chen; Jing Zhang; Chunbo Duan; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

Air permeability variation of compacted loess: effects of soil basic properties and dry-wet cycles - Shi-Feng Lu; Xiao-Pei Guo; Xing-Rui Wang; Zi-Jing Han; Ling Xu; Xiao-Lin Huang; Lu Zuo (Bulletin of Engineering Geology and the Environment, 2024)

Quantitative Applications of Weather Satellite Data for Nowcasting: Progress and Challenges - Jun Li; Jing Zheng; Bo Li; Min Min; Yanan Liu; Chian-Yi Liu; Zhenglong Li; W. Paul Menzel; Timothy J. Schmit; John L. Cintineo; Scott Lindstrom; Scott Bachmeier; et al. (Journal of Meteorological Research, 2024)

Enhanced lipid productivity of Monoraphidium strains in co-cultures and their potential for biodiesel production - Yimeng Lin; Jing Xu; Jixin Liu; Han Wang; Jingping Ge; Wenxiang Ping (Algal Research, 2024)

Long-term PM1 exposure and hypertension hospitalization: A causal inference study on a large community-based cohort in South China - Yuqin Zhang; Shirui Chen; Jing Wei; Jie Jiang; Xiao Lin; Ying Wang; Chun Hao; Wenjing Wu; Zhupei Yuan; Jie Sun; Han Wang; Zhicheng Du; et al. (Science Bulletin, 2024)

Association of blood cadmium levels and all-cause mortality among adults with rheumatoid arthritis: The NHANES cohort study - Haobiao Liu; Mian Liu; Lichun Qiao; Zhihao Yang; Yujie He; Miaoye Bao; Xue Lin; Jing Han (Journal of Trace Elements in Medicine and Biology, 2024)

Development of magnetic fluorescence aptasensor for sensitive detection of saxitoxin based on Fe3O4@Au-Pt nanozymes - Lin Zhu; Wei Zeng; Yueqing Li; Yu Han; Jing Wei; Long Wu (Science of The Total Environment, 2024)

The Pacific-North American teleconnection in the Cenozoic - Zhibo Li; Yongyun Hu; Jian Zhang; Xiang Li; Jiaqi Guo; Jiawenjing Lan; Qifan Lin; Shuai Yuan; Mengyu Wei; Zihan Yin; Qiang Wei; Xiujuan Bao; et al. (Global and Planetary Change, 2024)

UV-induced photodegradation of emerging para-phenylenediamine quinones in aqueous environment: Kinetics, products identification and toxicity assessments - Wei Wang; Guodong Cao; Jing Zhang; Han Qiao; Huankai Li; Biwei Yang; Yanyan Chen; Lin Zhu; Yuecheng Sang; Lei Du; Zongwei Cai (Journal of Hazardous Materials, 2024)

An efficient approach for identifying important biomarkers for biomedical diagnosis - Jing-Wen Huang; Yan-Hong Chen; Frederick Kin Hing Phoa; Yan-Han Lin; Shau-Ping Lin (BioSystems, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Maternal serum neonicotinoids during early-mid pregnancy and congenital heart diseases in offspring: An exploratory study - Yanji Qu; Adela Jing Li; Xiaoqing Liu; Shao Lin; Michael S. Bloom; Ximeng Wang; Xiaohong Li; Hui Wang; Fengzhen Han; Xiangmin Gao; Yong Wu; Kaiqin Huang; et al. (Environmental Pollution, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

The changes and correlation of IL-6 and oxidative stress levels in RAW264.7 macrophage cells induced by PAHs in PM2.5 - Jiaxin Liu; Hongqiu Li; Ziwei Guo; Xiang Xiao; Angelo Viscardi; Rongqi Xiang; Haobiao Liu; Xue Lin; Jing Han (Environmental Geochemistry and Health, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Circular economy strategies in supply chains, enhancing resource efficiency and sustainable development goals - Jing Qi Gao; Ding Li; Guang Hui Qiao; Qiao Ran Jia; Shi Ru Li; Han Lin Gao (Environmental Science and Pollution Research, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Fast ion/electron transport enabled by MXene confined bimetallic sulfides with heterostructure toward highly effective lithium/sodium storage - Yun-Lei Hou; Jing-Zhou Chen; Bo-Han Zhang; Hua-Ying Wang; Wan-Xin Wen; Dong-Lin Zhao (Chemical Engineering Journal, 2024)

Red blood cell membrane biomimetic nanoprobes for ratiometric imaging of reactive oxygen species level in atherosclerosis - Bo Liu; Gui-Mei Han; Dong-Xia Wang; Ding-Bin Liu; An-An Liu; Jing Wang; Yu-Ling Xiao; Lin Yuan; De-Ming Kong (Chemical Engineering Journal, 2024)

Discovery and verification of bitter components in Panax notoginseng based on the integrated strategy of pharmacophore model, system separation and bitter tracing technology - Jing Yang; Min Qiu; Tai Lu; Shangdong Yang; Ji Yu; Junzhi Lin; Hongyan Ma; Zhiping Guo; Zhencai Chen; Xue Han; Dingkun Zhang (Food Chemistry, 2023)

Analysis of volatile organic compounds and potential odour compounds in food contact paperboard using headspace two-dimensional GC-QTOF-MS - Dan Li; Ying Zeng; Zhi-Kang Ye; Han-Ke Li; Yu-Zhe Li; Ben Dong; Qi-Zhi Su; Qin-Bao Lin; Jing Xiao; Huai-Ning Zhong (Food Additives & Contaminants: Part A, 2023)

Probiotics ameliorate benzene-induced systemic inflammation and hematopoietic toxicity by inhibiting Bacteroidaceae-mediated ferroptosis - Lei Zhang; Huiwen Kang; Wei Zhang; JingYu Wang; Ziyan Liu; Jiaru Jing; Lin Han; Ai Gao (Science of The Total Environment, 2023)

Investigation of the effects of chemical modification and oxidative aging on the properties and compatibility of rubber asphalt based on thermodynamic principles - Jing Li; Hao Jiang; Fuhu Han; Zibo Lin; Zhenxia Zhao; Xin Jin; Yu Liu (Journal of Cleaner Production, 2023)

Disrupted in Schizophrenia 1 Reverse Ectopic Migration of Neural Precursors in Mouse Hilus After Pilocarpine-Induced Status Epilepticus - Lu Chen; Jing Xu; Lin Zhu; Puying Xu; Lvhua Chang; Yanbing Han; Qian Wu (Molecular Neurobiology, 2023)

Oxidative stress-affected ACSL1 hydroxymethylation triggered benzene hematopoietic toxicity by inflammation and senescence - Ziyan Liu; Xiaoli Guo; Wei Zhang; Jingyu Wang; Lei Zhang; Jiaru Jing; Lin Han; Ai Gao (Food and Chemical Toxicology, 2023)

Single and Combined Effects of Short-Term Selenium Deficiency and T-2 Toxin-Induced Kidney Pathological Injury Through the MMPs/TIMPs System - Ziwei Guo; Mumba mulutula Chilufya; Huan Deng; Lichun Qiao; Jiaxin Liu; Xiang Xiao; Yan Zhao; Xue Lin; Haobiao Liu; Rongqi Xiang; Jing Han (Biological Trace Element Research, 2023)

Permanganate activation by glucose-derived carbonaceous materials for highly efficient degradation of phenol and p-nitrophenol: Formation of hydroxyl radicals and multiple roles of carbonaceous materials - Kaikai Zhang; Muhan Qin; Chih-Ming Kao; Jiayu Deng; Jing Guo; Qiong Guo; Jing Hu; Wei-Han Lin (Chemosphere, 2023)

The gut-brain axis involved in polystyrene nanoplastics-induced neurotoxicity via reprogramming the circadian rhythm-related pathways - Huiwen Kang; Wei Zhang; Jiaru Jing; Danyang Huang; Lei Zhang; Jingyu Wang; Lin Han; Ziyan Liu; Ziyan Wang; Ai Gao (Journal of Hazardous Materials, 2023)

Degradation of indole via a two-component indole oxygenase system from Enterococcus hirae GDIAS-5 - Jun-Jin Deng; Jing-Yi Hu; Xue-ying Han; Yang Li; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li (Journal of Hazardous Materials, 2023)

In situ generated of hybrid interface in poly(1,3-dioxolane) quasi solid electrolyte and extended sulfone cosolvent for lithium-metal batteries - Bo-Han Zhang; Wan-Xin Wen; Hua-Ying Wang; Yun-Lei Hou; Jing-Zhou Chen; Dong-Lin Zhao (Chemical Engineering Journal, 2023)

Cooling effects of wetland parks in hot and humid areas based on remote sensing images and local climate zone scheme - Lin Liu; Huiyu He; Yuhong Cai; Jian Hang; Jing Liu; Liru Liu; Pei Jiang; Han He (Building and Environment, 2023)

Research on carbon footprint measurement and emissions reduction optimization of the beer supply chain in China - Jing Chen; Han Bao; Lin-Ke Pei (Environmental Science and Pollution Research, 2023)

Removal of chemical oxygen demand and ammonia nitrogen from high salinity tungsten smelting wastewater by one-step electrochemical oxidation: From bench-scale test, pilot-scale test, to industrial test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Huanjun Bao; Meirong Wu; Lei Yang; Gaogui Jing; Haisheng Han; Chenyang Zhang; Xiaoyun Jiang; Songlin Wang; Wei Ding; et al. (Journal of Environmental Management, 2023)

A gluten degrading probiotic Bacillus subtilis LZU-GM relieve adverse effect of gluten additive food and balances gut microbiota in mice - Aman Khan; Shiqing Li; Huawen Han; Wei-Lin Jin; Zhenmin Ling; Jing Ji; Shazia Iram; Pu Liu; Sa Xiao; El-Sayed Salama; Xiangkai Li (Food Research International, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Effect of curcumin on the formation of polycyclic aromatic hydrocarbons in grilled chicken wings - Huixin Tian; Jing Yu; Min Li; Jing Li; Yifeng Lu; Xiaobo Yu; Shaoyan Lin; Xianming Zeng; Xinglian Xu; Minyi Han (Food Chemistry, 2023)

Effect of functionalized nanodiamonds and surfactants mediation on the nanofiltration performance of polyamide thin-film nanocomposite membranes - T.M. Subrahmanya; Jing-Yang Lin; Januar Widakdo; Hannah Faye M. Austria; Owen-Setiawan; Yu-Hsuan Chiao; Tsung-Han Huang; Wei-Song Hung; Hideto Matsuyama; Kueir-Rarn Lee; Juin-Yih Lai (Desalination, 2023)

Selenium nanoparticles: Properties, preparation methods, and therapeutic applications - Xiang Xiao; Huan Deng; Xue Lin; Ahmed Sameir Mohamed Ali; Angelo Viscardi; Ziwei Guo; Lichun Qiao; Yujie He; Jing Han (Chemico-Biological Interactions, 2023)

An extracellular protease containing a novel C-terminal extension produced by a marine-originated haloarchaeon - Dong Han; Jing Hou; Heng-Lin Cui (Frontiers in Marine Science, 2023)
Marine microorganisms have long been acknowledged as a significant reservoir of enzymes required for industrial use. In this study, a novel extracellular protease Hsl HlyB derived from marine-originated haloarchaeon Halostella pelagica DL-M4 T was identified. Hsl HlyB contained polycystic kidney disease (PKD) domain and pre-peptidase C-terminal (PPC) domain at the C-terminus. Truncation and replacement of the C-terminal extension (CTE) of Hsl HlyB demonstrated the importance of the CTE in maintaining the protease activity secreted by haloarchaeon. Hsl HlyB and Hsl HlyBΔCTE were expressed in Escherichia coli BL21(DE3), and purified by high-affinity column refolding and gel filtration chromatography. The molecular masses of Hsl HlyB and Hsl HlyBΔCTE were 42 kDa and 20 kDa, respectively. The optimum catalytic reaction conditions were 50°C, pH 8.5, NaCl 3.5 M and 50°C, pH 7.5, NaCl 3 M, respectively. They showed good stability and hydrolysis capabilities towards a wide range of protein substrates. Hsl HlyBΔCTE showed higher catalytic reaction rate and better thermal stability than the wild type against azocasein and tetrapeptide substrate. The hydrolysates of soybean protein hydrolyzed by Hsl HlyBΔCTE had smaller average molecular masses and shorter average peptide chain lengths than those by Hsl HlyB. These results indicated the diversity of halolysins from marine-originated haloarchaea to harness organic nitrogen in the marine environment and provided promising candidates for application in various industries.

Levels, distribution, childhood exposure assessment, and influencing factors of polybrominated diphenyl ethers (PBDEs) in household dust from nine cities in China - Jing Qi; Xiaoli Wang; Lin Fan; Shuhan Gong; Xinqi Wang; Chong Wang; Li Li; Hang Liu; Yun Cao; Mengmeng Liu; Xu Han; Liqin Su; et al. (Science of The Total Environment, 2023)

Discovery of uncommon terpenoids from the South China Sea soft coral Sinularia scabra - Kui Wang; Jing Liu; Jian Huang; Xue Leng; Te Li; Han Ouyang; Wenhan Lin; Xia Yan; Shan He (Phytochemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

The role of N6-methyladenosine modification in benzene-induced testicular damage and the protective effect of melatonin - Lin Han; Jingyu Wang; Lei Zhang; Jiaru Jing; Wei Zhang; Ziyan Liu; Ai Gao (Chemosphere, 2023)

Levels, distribution, sources and children health risk of PAHs in residential dust: A multi-city study in China - Xinqi Wang; Xiaoli Wang; Jing Qi; Shuhan Gong; Chong Wang; Li Li; Lin Fan; Hang Liu; Yun Cao; Mengmeng Liu; Xu Han; Liqin Su; et al. (Science of The Total Environment, 2023)

Genus unclassified_Muribaculaceae and microbiota-derived butyrate and indole-3-propionic acid are involved in benzene-induced hematopoietic injury in mice - Jingyu Wang; Lin Han; Ziyan Liu; Wei Zhang; Lei Zhang; Jiaru Jing; Ai Gao (Chemosphere, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Metal ions synergize with gangue minerals to remove residual sodium oleate from mineral processing wastewater - Xiangsong Meng; Min Jiang; Shangyong Lin; Zhiyong Gao; Haisheng Han; Li Wang; Chenyang Zhang; Ruohua Liu; Huanjun Bao; Meirong Wu; Gaogui Jing; Wei Sun (Journal of Cleaner Production, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Failure mode and genesis of bare dispersive soil slope in the cold dry region: insights from Southwest Songnen Plain, China - Yan Han; Qing Wang; Cencen Niu; Huicheng Fu; Jing Liu; Mengxia Han; Sen Lin; Muhammad Ammar (Bulletin of Engineering Geology and the Environment, 2022)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Optimized thyroid transcription factor-1 core promoter-driven microRNA-7 expression effectively inhibits the growth of human non-small-cell lung cancer cells - Shipeng Chen; Lian Guan; Xu Zhao; Jing Yang; Longqing Chen; Mengmeng Guo; Juanjuan Zhao; Chao Chen; Ya Zhou; Yong Han; Lin Xu (Journal of Zhejiang University-SCIENCE B, 2022)

New phenolic glycosides from Anemone chinensis Bunge and their antioxidant activity - Zeng-Guang Zhang; Yuan-Yuan Li; Bin Lin; Pei-Pei Guan; Yu Mu; Wen-Jun Qiao; Jing-Sheng Zhang; Xue-Shi Huang; Li Han (Natural Product Research, 2022)

Progress of Selenium Deficiency in the Pathogenesis of Arthropathies and Selenium Supplement for Their Treatment - Huan Deng; Haobiao Liu; Zhihao Yang; Miaoye Bao; Xue Lin; Jing Han; Chengjuan Qu (Biological Trace Element Research, 2022)

First report of Sclerotinia sclerotiorum on Atractylodes lancea in China - Feng Han; Jing Huang; Maoxiang Lin; Xuhong Song (Journal of Plant Pathology, 2022)

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Delayed rFGF21 Administration Improves Cerebrovascular Remodeling and White Matter Repair After Focal Stroke in Diabetic Mice - Yinghua Jiang; Jinrui Han; Yadan Li; Yinga Wu; Ning Liu; Samuel X. Shi; Li Lin; Jing Yuan; Shusheng Wang; Ming-Ming Ning; Aaron S. Dumont; Xiaoying Wang (Translational Stroke Research, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Consistency correction of echo intensity data for multiple radar systems and its application in quantitative estimation of typhoon precipitation - Shuai Zhang; Jing Han; Bingke Zhao; Zhigang Chu; Jie Tang; Limin Lin; Xiaoqin Lu; Jiaming Yan (Frontiers of Earth Science, 2022)

Synthesis of Silver- and Strontium-Substituted Hydroxyapatite with Combined Osteogenic and Antibacterial Activities - Yunfei Li; Wenying Wang; Jing Han; Zirui Li; Qiuxiang Wang; Xue Lin; Kun Ge; Guoqiang Zhou (Biological Trace Element Research, 2022)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Whole brain volume and cortical thickness abnormalities in Wilson’s disease: a clinical correlation study - Yukun Song; Lin Zou; Jing Zhao; Xiangxue Zhou; Yingqian Huang; Haishan Qiu; Haiwei Han; Zhiyun Yang; Xunhua Li; Xiaoying Tang; Jianping Chu (Brain Imaging and Behavior, 2021)

Porcine circovirus type 2 (PCV2) infection in Hebei Province from 2016 to 2019: a retrospective study - Lei Han; Guang-fu Yuan; Shao-jie Chen; Fei Dai; Lin-shan Hou; Jing-hui Fan; Yu-zhu Zuo (Archives of Virology, 2021)

Effects of diethyl aminoethyl hexanoate on the physiology and selenium absorption of grape seedlings - Lei Liu; Jiaxi Han; Lili Deng; Huixuan Zhou; Yuhui Bie; Qianhe Jing; Lijin Lin; Jin Wang; Ming’an Liao (Acta Physiologiae Plantarum, 2021)

A luminescent Zn(II)-Containing Complex: Selective Sensing of Cr(VI) Anion and Application Values on Tuberculosis Care Through Increasing the Antibacterial Response of Macrophages - Jin-Chao Mao; Jin-Jing Hong; Ming-Zheng Lin; Feng Han; Dong Li (Journal of Fluorescence, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Complete mitochondrial genome of the freshwater fish Acrossocheilus longipinnis (Teleostei: Cyprinidae): genome characterization and phylogenetic analysis - Xiao-Jing Hou; Hung-Du Lin; Wen-Qiao Tang; Dong Liu; Chiao-Chuan Han; Jin-Quan Yang (Biologia, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Exploring global food security pattern from the perspective of spatio-temporal evolution - Jianming Cai; Enpu Ma; Jing Lin; Liuwen Liao; Yan Han (Journal of Geographical Sciences, 2020)

Effects of Temperature on Bacterial Biodiversity and Qualities of Fermented Yucha Products - Shuai Wang; Jing Han; Jingbo Zhang; Xinping Lin; Huipeng Liang; Shengjie Li; Xiuping Dong; Chaofan Ji (Journal of Aquatic Food Product Technology, 2020)

Comparative analysis of a panel of biomarkers related to protein phosphatase 2A between laryngeal squamous cell carcinoma tissues and adjacent normal tissues - Han-ying Wang; Hui Yuan; Jing-hui Liu; Bei-lei Wang; Kai-lun Xu; Pu Huang; Zhi-hong Lin; Li-hong Xu (Journal of Zhejiang University-SCIENCE B, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Dual therapy with clopidogrel and aspirin prevents early neurological deterioration in ischemic stroke patients carrying CYP2C19*2 reduced-function alleles - Jing Lin; Zhao Han; Chun Wang; Xingyang Yi; Zhenxiao Chai; Qiang Zhou; Ruyue Huang (European Journal of Clinical Pharmacology, 2018)

Spa therapy (balneotherapy) relieves mental stress, sleep disorder, and general health problems in sub-healthy people - Bei Yang; Qi-zhong Qin; Ling-li Han; Jing Lin; Yu Chen (International Journal of Biometeorology, 2018)

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Qiuan Zhu; Changhui Peng; Philippe Ciais; Hong Jiang; Jinxun Liu; Philippe Bousquet; Shiqin Li; Jie Chang; Xiuqin Fang; Xiaolu Zhou; Huai Chen; Shirong Liu; et al. (Global Change Biology, 2017)
Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Follistatin-like protein 1 suppressed pro-inflammatory cytokines expression during neuroinflammation induced by lipopolysaccharide - Kai-Yuan Cheng; Yi Liu; Ying-Guang Han; Jing-Kun Li; Jia-Lin Jia; Bin Chen; Zhi-Xiao Yao; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Characterization of the complete chloroplast genome of Platycarya strobilacea (Juglandaceae) - Jing Yan; Kai Han; Shuyun Zeng; Peng Zhao; Keith Woeste; Jianfang Li; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

Molecular signal networks and regulating mechanisms of the unfolded protein response - Jing Gong; Xing-zhi Wang; Tao Wang; Jiao-jiao Chen; Xiao-yuan Xie; Hui Hu; Fang Yu; Hui-lin Liu; Xing-yan Jiang; Han-dong Fan (Journal of Zhejiang University-SCIENCE B, 2017)

Effect of LA on the Growth and Development of the Main Organs in Female Mice - Xiuyuan He; Feng Lin; Yongtao Li; Yuxia Chen; Jing Li; Linlin Guo; Xuelei Han; Huan Song (Biological Trace Element Research, 2017)

Oceanic currents drove population genetic connectivity of the brown alga Sargassum thunbergii in the north‐west Pacific - Jing‐Jing Li; Zi‐Min Hu; Xu Gao; Zhong‐Min Sun; Han‐Gil Choi; De‐Lin Duan; Hikaru Endo (Journal of Biogeography, 2017)
Aim Oceanic currents are among the most pervasive hydrodynamic features in shaping community dynamics, population connectivity and phylogeographical structure of intertidal species. Here, we test whether population structure and biogeographical gradients of genetic diversity in the brown alga Sargassum thunbergii are correlated with oceanic currents in the north‐west Pacific ( NWP ). Location North‐west Pacific (25.07°N–43.36°N). Methods Nuclear internal transcribed spacer‐2 and mitochondrial cox 3 sequences were obtained from 835 and 810 individuals of S. thunbergii respectively. Parsimony networks and phylogenetic trees (maximum parsimony and Bayesian inference) were constructed to evaluate phylogeographical structure. Pairwise F ST estimates and analyses of molecular variance ( AMOVA ) at various hierarchical levels (latitude, longitude, marine provinces, biogeographical basins and zoogeographical zones) were conducted to elucidate population genetic differentiation. migrate software was used to estimate the number of migrants between adjacent populations. Results Several lines of evidence indicate that S. thunbergii is characterized by shallow population structure. Geographical distances do not correlate with population pairwise genetic differentiations. The corridor/stepping‐stone model‐based coalescent analyses reveal high levels of asymmetric gene flow among S. thunbergii populations, with the numbers of migrants largely corresponding to the directions of oceanic current systems in the NWP . Genetic signatures also indicate that Jeju Island, Korea might act as a transition zone for dispersal of S. thunbergii in the NWP driven by the Kuroshio Current, thus facilitating subsequent transportation northward into the Sea of Japan and the Yellow‐Bohai Sea. Main conclusions Population genetic homogeneity in S. thunbergii was mainly structured by oceanic currents rather than palaeoclimatic events. Our study illustrates an important phylogeographical case of how coastal hydrodynamic factors contributed to population connectivity and geographical shifts of genetic diversity for marine organisms without a pelagic stage.

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

Induced growth promotion and higher salt tolerance in the halophyte grass Puccinellia tenuiflora by beneficial rhizobacteria - Shu-Qi Niu; Hui-Ru Li; Paul W. Paré; Mina Aziz; Suo-Min Wang; Huazhong Shi; Jing Li; Qing-Qing Han; Shi-Qian Guo; Jian Li; Qiang Guo; Qing Ma; et al. (Plant and Soil, 2016)

Impact of heat waves on nonaccidental deaths in Jinan, China, and associated risk factors - Jun Zhang; Shouqin Liu; Jing Han; Lin Zhou; Yueling Liu; Liu Yang; Ji Zhang; Ying Zhang (International Journal of Biometeorology, 2016)

Gene characterization and transcription analysis of two new ammonium transporters in pear rootstock (Pyrus betulaefolia) - Hui Li; Jin-Long Han; You-Hong Chang; Jing Lin; Qing-Song Yang (Journal of Plant Research, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Haloarchaeobius amylolyticus sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Xin-Juan Sun; Xi Liang; Xiao-Jing Chen; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2015)

A γ-Glutamylcysteine Synthetase Gene from Pyrus calleryana Is Responsive to Ions and Osmotic Stresses - Hui Li; Jin-long Han; Jing Lin; Qing-song Yang; You-hong Chang (Plant Molecular Biology Reporter, 2015)

Blockade of the Activation of T Cells Around β-Cell by the Targeted CTLA-4 Ig at the Surface of β-Cell - Wei Qu; Lin Li; Chendong Han; Meihua Li; Jing Wang; Chaohui Yin; Jing Zhang; Zhaoshun Jiang (Cell Biochemistry and Biophysics, 2015)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

Purification and characterization of a laccase from Coprinopsis cinerea in Pichia pastoris - Bo Wang; Lijuan Wang; Yaqiu Lin; Qing Han; Jing Han; Jianjie Gao; Yongsheng Tian; Wei Zhao; Rihe Peng; Quanhong Yao (World Journal of Microbiology and Biotechnology, 2014)

The Use of Borneol as an Enhancer for Targeting Aprotinin-Conjugated PEG-PLGA Nanoparticles to the Brain - Lin Zhang; Limei Han; Jing Qin; Weiyue Lu; Jianxin Wang (Pharmaceutical Research, 2013)

Cytology of infection of apple leaves by Diplocarpon mali - Hua Zhao; Qingmei Han; Jie Wang; Xiaoning Gao; Chang-Lin Xiao; Jing Liu; Lili Huang (European Journal of Plant Pathology, 2013)

Erratum to: Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

TFF3 mediated induction of VEGF via hypoxia in human gastric cancer SGC-7901 cells - Bayasi Guleng; Jia Han; Jin-Qiu Yang; Qing-Wen Huang; Jian-Kun Huang; Xiao-Ning Yang; Jing-Jing Liu; Jian-Lin Ren (Molecular Biology Reports, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Hydrodynamic change recorded by diatoms in sediments of Liuxihe Reservoir, southern China - Jing Liu; Zhangwen Lin; Huajun Zhang; Bo-Ping Han (Journal of Paleolimnology, 2012)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Genetic analysis of ABCG2 gene C421A polymorphism with gout disease in Chinese Han male population - Binbin Wang; Zhimin Miao; Shiguo Liu; Jing Wang; Shiyi Zhou; Lin Han; Dongmei Meng; Yunlong Wang; Changgui Li; Xu Ma (Human Genetics, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Cloning and sequence analysis of the gene encoding 19-kD subunit of Complex I from Dunaliella salina - Yi Liu; Dai Rong Qiao; Hong Bo Zheng; Xu Lan Dai; Lin Han Bai; Jing Zeng; Yi Cao (Molecular Biology Reports, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)